Glass melting experiments in the reconstruction of glass furnace from the 9th century - Staššíková-Štukovská, Danica; Galusková, Dagmar; Plško, Alfonz (Archeologia Polski, 2020)
The authors research and publish the results from a glass melting experiments conducted in a reconstruction of a historic wood-fired furnace from the 9th c. during the 2017–2019 period. The experiments focused on soda-lime glass and were implemented as pilot for the planned, long-term and annual experimentations in the Archeopark in Hanušovce nad Topľou. Experimental glass batches were weighed according to the composition of glass from archaeological samples from the 9th c., as well as according to the model soda ash glass. The aim was to obtain experimental data to verify archaeometric research of historical glass. The study focused on the possible use of a wood-fired furnace in the melting glass from glass batches, the effects of ash on the composition of glass, remelting of glass cullet, penetration of elements from crucible and flue gases into molten glass, causes of different quality of glass remelting or colouring with added CuO and MnO. Another aim of the study was to compare the results of the glass analyses from the SEM/EDS and XRF method, which we later interpret in historical contexts.